Analisis Overcrowded di Instalasi Gawat Darurat Rumah Sakit Umum Daerah Raden Mattaher Provinsi Jambi - Andi Subandi; Dwi Noerjoedianto (PERSPEKTIF, 2021)
This study aims to see the density of patient visits at the Raden Mattaher Regional Hospital by using the National Emergency Department Overcrowded Scale (Nedocs). The method used in this study is an analytical survey to assess the role and function of an emergency room management and to analyze the management of patients in the emergency room at the Raden Mattaher Regional General Hospital (RSUD), Jambi Province. The results of this study indicate the average overcrowded rating in the ER at Raden Mattaher Hospital Jambi, which is in the range of 61-100 with the assessment category Very busy but not too full (extremely busy but not overcrowded). According to the Ministry of Health, the calculation of the need for human resources for nurses, the number of nurses in the ER at Raden Mattaher Hospital is short of 4 people, and not all of them are emergency certified. Based on the research results, it can be concluded that the policy decision making has been implemented but it has not been implemented properly. Furthermore, regarding the density in the emergency room during patient visits, the Raden Mattaher Regional Hospital provides a step solution to hospital management.